The Spiritual Approach to_x000D_ Systemic Family Therapies - (:unkn) unknown (My University, 2020)
The concept of spirituality has started being included in therapy settings due to the new paradigmsshowing developments in the world of psychology in the late 20th century and in the 21st century.When examining the literature, many articles and books are seen to have been published relatedto the topic, and most of the studies have been carried out abroad. These performed studies havecontributed new concepts and information to the literature by revealing how the concept ofspirituality can be integrated with family therapies. This study has been prepared for the purposesof drawing the attention of researchers who conduct studies in Turkey based on systemic familytherapy and of specialists who plan therapy sessions based the relevant theory to the topic andto provide the literature with a topic that finds no examples in the literature of Turkey. How theconcept of spirituality can be used in harmony with the systemic family therapy approach and whatthe techniques of the spirituality-based systemic family therapy are have been prepared by beingbased on the many studies that have been published abroad. Before beginning the study, theoreticalinformation and basic concepts primarily about systemic family therapies are provided, and thenit moves on to spirituality-oriented systemic family therapy by briefly mentioning the concept ofspirituality. How the concept of spirituality can be applied to systemic family therapy and the pointsand ethical situations to which counselors need to pay attention are also mentioned. Lastly, samplecases are shared by providing information about the techniques of using religious stories and spiritualdialogue, these techniques being used in spirituality-oriented systemic family therapies.

Yirminci yüzyılın sonlarında ve yirmi birinci yüzyılda psikoloji dünyasında gelişme gösteren yeni_x000D_ paradigmalar sayesinde maneviyat kavramı terapi ortamlarına dahil edilmeye başlamıştır. Alan yazın_x000D_ incelendiğinde yapılan çalışmaların çoğunlukla yurtdışında gerçekleştirildiği ve konuyla ilgili birçok_x000D_ makale ve kitap yayınlandığı görülmektedir. Yapılan bu çalışmalar sayesinde maneviyat kavramının_x000D_ aile terapilerine nasıl entegre edilebileceği ortaya konularak, yeni kavram ve bilgilerle literatüre_x000D_ katkı sağlanmıştır. Bu çalışma ülkemizde sistemik aile terapisi kuramına dayalı çalışmalar yapan_x000D_ araştırmacıların ya da ilgili kurama dayalı olarak terapi seanslarını planlayan uzmanların ilgilerinin_x000D_ konuya çekilmesi ve ülkemiz alan yazınında örnekleri bulunmayan bir konuyu literatüre kazandırmak_x000D_ amacıyla hazırlanmıştır. Maneviyat kavramının sistemik aile terapisi yaklaşımına uygun olarak nasıl_x000D_ kullanılabileceği ve manevi yaklaşımlı sistemik aile terapisi tekniklerinin neler olduğu yurt dışında_x000D_ yayınlanmış pek çok çalışma temel alınarak hazırlanmıştır. Çalışmadan öncelikle sistemik aile terapileri_x000D_ hakkında kuramsal bilgiler ve temel kavramlar verilmiş, daha sonra maneviyat kavramından kısaca_x000D_ bahsedilerek manevi yönelimli sistemik aile terapisine geçilmiştir. Sistemik aile terapisine maneviyat_x000D_ kavramının nasıl uyarlanabileceği, danışmanların dikkat etmeleri gereken noktalar ve etik durumlara_x000D_ değinilmiştir. Son manevi yönelimli sistemik aile terapilerinde kullanılan “Dini Hikayelerin Kullanımı”_x000D_ ve “Manevi Diyalog” tekniklerin hakkında bilgi verilerek örnek vakalar paylaşılmıştır.
Sistemik Aile Terapileri ’ne Manevi Yaklaşım